CLINICAL AND PHARMACOECONOMIC EFFICACY OF NATIONAL LACTOBACILLUS-BASED PROBIOTICS IN COMPLEX THERAPY FOR ACUTE ENTERIC INFECTIONS IN CHILDREN - N.V. Gonchar; L.V. Berezina; S.V. Mogilina; Yu.M. Il'kovich (Union of pediatricians of Russia, 2010)
Active use of probiotic medications in children with acute enteric infections (AEI) does not always result in noticeable improvement of therapy results, which triggers the need for a study of pharmacoeconomic efficacy of using probiotics. The results of complex therapy for AEI in infants using lactobacillus-based prebiotics and conventional therapy were compared. Key clinical criteria of therapy for AEI were: reduction in inflammatory intestine modifications, elimination of Klebsiella pneumoniae, restoration of indigenous microflora. The results of the conducted study helped identify antagonism of Vitaflora against K. pneumoniae, a positive influence on colitis syndrome progress, as well as identify Biobacton's impact on the restoration of intestine microbiocenosis.Key words: Acute enteric infections, children, infancy, therapy, prebiotics, pharmacoeconomic efficacy. (Pediatric Pharmacology. - 2010; 7(6):10-15)